Super-resolution imaging of live sperm reveals dynamic changes of the actin cytoskeleton during acrosomal exocytosis - Romarowski, Ana (2018)
Filamentous actin (F-actin) is a key factor in exocytosis in many cell types. In mammalian sperm, acrosomal exocytosis (denoted the acrosome reaction or AR), a special type of controlled secretion, is regulated by multiple signaling pathways and the actin cytoskeleton. However, the dynamic changes of the actin cytoskeleton in live sperm are largely not understood. Here, we used the powerful properties of SiR-actin to examine actin dynamics in live mouse sperm at the onset of the AR. By using a combination of super-resolution microscopy techniques to image sperm loaded with SiR-actin or sperm from transgenic mice containing Lifeact-EGFP, six regions containing F-actin within the sperm head were revealed. The proportion of sperm possessing these structures changed upon capacitation. By performing live-cell imaging experiments, we report that dynamic changes of F-actin during the AR occur in specific regions of the sperm head. While certain F-actin regions undergo depolymerization prior to the initiation of the AR, others remain unaltered or are lost after exocytosis occurs. Our work emphasizes the utility of live-cell nanoscopy, which will undoubtedly impact the search for mechanisms that underlie basic sperm functions.